Palladium‐Catalyzed Asymmetric Conjugate Addition of Arylboronic Acids to Heterocyclic Acceptors. Issue 1 (3rd December 2012) - Holder, Jeffrey C.; Marziale, Alexander N.; Gatti, Michele; Mao, Bin; Stoltz, Brian M.
<x xml:space="preserve">Abstract</x> Flava Flavanone: Asymmetric conjugate additions to chromones and 4‐quinolones are reported utilizing a single catalyst system formed in situ from Pd(OCOCF3)2 and (S)‐tBuPyOX. Notably, these reactions are performed in wet solvent under ambient atmosphere, and employ readily available arylboronic acids as the nucleophile, thus providing ready access to these asymmetric heterocycles (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>